(untitled) (Research, Society and Development, 2026)
The incorporation of Artificial Intelligence (AI)-based tools in Human Resource Management has transformed the way organizations recruit, evaluate, and retain people. Processes historically reliant on subjective judgment are increasingly supported by systems capable of processing large volumes of data and identifying behavioral patterns. This article aims to analyze, through a systematic narrative review, the main contributions and challenges of AI in HRM, focusing on effects related to organizational justice perceptions, institutional trust, and the psychological contract. The methodology involved searches in the Web of Science, Scopus, PsycINFO, and SciELO databases, covering the period from 2010 to 2025. Results indicate that while AI expands analytical capacity and improves operational indicators, its implementation carries significant risks: reproduction of historical biases, erosion of procedural justice perceptions, and disruption of the psychological contract when algorithmic criteria are not communicated transparently. The conclusion is that organizational benefits of AI are real, but conditional on the existence of robust data governance structures, explicit ethical guidelines, and a commitment to preserving human judgment in high-impact decisions.